Effect of Remote Ischemic Preconditioning in Patients Undergoing Hepatectomy With Portal Triad Clamping: A Randomized Controlled Trial. (December 2019) - Liu, Xiaoqing; Cao, Longhui; Zhang, Tianhua; Guo, Rongping; Lin, Wenqian
Abstract : BACKGROUND: Remote ischemic preconditioning (RIPC) is reported to reduce liver injury in patients undergoing hepatectomy for colorectal liver metastasis, but its role is unclear in hepatocellular carcinoma patients with portal triad clamping during hepatectomy. METHODS: In this prospective, randomized trial, 140 patients with hepatocellular carcinoma undergoing liver resection requiring portal triad clamping were randomized to a RIPC group or a control group. Patients in the RIPC group received RIPC (3 cycles of 5-minute ischemia and 5-minute reperfusion in right upper limb with cuff pressure at 30 kPa [225 mm Hg]) approximately 10 minutes after induction of anesthesia. In the control group, patients received sham RIPC (the cuff was not inflated). The primary outcome was the postoperative peak level of total bilirubin (TBIL) and was analyzed with the independent t test. Secondary outcomes were liver function test at postoperative days 1, 3, and 5; postoperative morbidity and mortality during the first month; and the length of postoperative hospital stay. RESULTS: Data from 136 patients (69 in the RIPC group and 67 in the control group) were analyzed. The RIPC group had on average a 5.9 μmol lower peak level of TBIL than the control group; the mean difference is −5.9, and the 95% confidence interval (CI) reverses to −17.9 to 6.1. There were no significant differences between the 2 groups in liver function test at postoperative days 1, 3, and 5; postoperative morbidity and mortality during the first month; and the length of postoperative hospital stay. CONCLUSIONS: We found no evidence that RIPC can reduce postoperative liver injury after hepatectomy.